2010
DOI: 10.4314/ajtcam.v7i2.50877
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards african traditional medicine and christian spiritual healing regarding treatment of epilepsy in a rural community of northern Tanzania

Abstract: Most people with epilepsy (PWE) live in developing countries with limited access to health care facilities. In sub-Saharan Africa with approximately 12 million PWE, 90% do not receive adequate medical treatment. In this context, traditional medicine, being easily accessible, plays an important role. However, in subSaharan Africa, studies on the attitude of people (both affected and not affected by epilepsy) towards traditional medicine for treatment of epilepsy are scarce. In this study, 167 people (59 PWE, 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
(18 reference statements)
3
29
0
1
Order By: Relevance
“…In the absence of CT the clinician may attempt to get serial T. solium cysticercosis antigen levels 89 The 'access gap' is caused by factors such as inconsistent access to health facilities with antiepileptic medication, lack of knowledge of affected people and their families, medical personnel and entire communities on the topic of epilepsy, traditional concepts as to the origin of epilepsy and resulting stigma towards people with epilepsy, among other factors. [96][97][98][99] This stigma was clearly demonstrated in a recent study from Zambia which showed that people with epilepsy are disadvantaged regarding social and economic matters compared to people with other chronic diseases without an attached stigma, such as asthma, diabetes mellitus, hypertension, and rheumatic heart disease. 100 The 'adherence gap' which describes the failure of compliance with antiepileptic medication often is due to lack of information and education of the patients and their families as well as lack of time and lack of knowledge on treatment of health personnel.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of CT the clinician may attempt to get serial T. solium cysticercosis antigen levels 89 The 'access gap' is caused by factors such as inconsistent access to health facilities with antiepileptic medication, lack of knowledge of affected people and their families, medical personnel and entire communities on the topic of epilepsy, traditional concepts as to the origin of epilepsy and resulting stigma towards people with epilepsy, among other factors. [96][97][98][99] This stigma was clearly demonstrated in a recent study from Zambia which showed that people with epilepsy are disadvantaged regarding social and economic matters compared to people with other chronic diseases without an attached stigma, such as asthma, diabetes mellitus, hypertension, and rheumatic heart disease. 100 The 'adherence gap' which describes the failure of compliance with antiepileptic medication often is due to lack of information and education of the patients and their families as well as lack of time and lack of knowledge on treatment of health personnel.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%
“…Adherence to antiepileptic medication not only is influenced by health service related factors but again by stigma towards people with epilepsy and by people's belief systems which may view epilepsy as caused by demoniac possession or punishment for sins, among others. [96][97][98][99] Those and other factors that may be responsible for the 'epilepsy treatment gap' have to be taken into consideration when dealing with people with epilepsy/epileptic seizures in subSaharan Africa, irrespective of the origin of the epileptic seizures.…”
Section: Difficulties Of Treating Ncc In Sub-saharan Africamentioning
confidence: 99%
“…[9] Winkler ve ark. [10] çalışmasına göre Tanzanya'da epilepsi hastalarınca uygulanan geleneksel tedaviler %9.6 geleneksel bitki tedavisi, %7.2 geleneksel manevi tedavi, %3.6 emetik özelliği olan bitki ile hastayı kusturma, %1.8 hastalığı kovma/çıkarma ve %34.1 dua etmedir.…”
Section: Discussionunclassified
“…The lack of awareness of local and international policy makers, poor infrastructure, long travel distances, the insufficient or only intermittent availability of antiepileptic medications, the lack of education among people with epilepsy, their families and the communities, the predominance of traditional belief systems and the scarcity of trained medical personnel may be responsible for this large treatment gap [39,40]. Another important but often neglected cause of this treatment gap is social stigma.…”
Section: Treatment Gap Of Epilepsy In Sub-saharan Africamentioning
confidence: 99%